2016
DOI: 10.1021/acsami.5b12591
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase-like Catalytic Activity of Copper-Mediated Protein–Inorganic Hybrid Nanoflowers and Nanofibers of β-Lactoglobulin and α-Lactalbumin: Synthesis, Spectral Characterization, Microscopic Features, and Catalytic Activity

Abstract: A free Cys-SH-containing protein, β-lactoglobulin (β-LG), and another protein not possessing the same, viz., apo-α-lactoglobulin (apo-α-LA), were used in studies to demonstrate the role of this amino acid, along with its secondary structure, in the formation of a protein dimer and a protein-inorganic hybrid nanoflower and in the creation of the peroxidase-like activity of the nanomaterials produced when the proteins were treated with varying Cu(2+) concentration under different pH conditions. An increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The catalytic measurements were conducted by monitoring the absorbance changes in spectrum mode after 10 min of the catalytic reaction in natural daylight. The absorbance of the resulting solution was measured at 500 nm, corresponding to the formation of quinone–imine complex …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic measurements were conducted by monitoring the absorbance changes in spectrum mode after 10 min of the catalytic reaction in natural daylight. The absorbance of the resulting solution was measured at 500 nm, corresponding to the formation of quinone–imine complex …”
Section: Methodsmentioning
confidence: 99%
“…The absorbance of the resulting solution was measured at 500 nm, corresponding to the formation of quinone-imine complex. [53] Characterization: A TEM (JEOL JEM-1200 EX) was used to observe morphology and structure of the samples at 100 kV. HRTEM images and EDX analysis were investigated by a FEI Tecnai G2 F20 high-resolution transmission electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting study by Thawari et al [120] on β-LG and apo-α-LA was reported on the effect of copper (II) ions on the formation of protein dimers and the catalytic activity of the formed nanobiomaterials, which were inorganic hybrid nanomaterials in its nature. Nanostructures in the form of nanoflowers and nanofibers combined with copper-LG and copper-LA with Cu as the inorganic part exhibited peroxidase-like catalytic activity.…”
Section: Changes In Bioactivity After Metal Interactionsmentioning
confidence: 99%
“…They created novel hybrid nanoflowers (hNFs) with much greater enzymatic activity and stability than those obtained with free enzymes. Some researchers have prepared various kinds of organicinorganic nNFs and used them for different applications (Sun et al, 2014;Liang et al, 2015;Huang et al, 2015;Somturk et al, 2015;Altinkaynak et al 2016a;Altinkaynak et al, 2016b;Ariza-Avidad et al, 2016;Thawari et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%